ESRA19-0333 A multicentre retrospective observational study comparing the effectiveness of serratus anterior plane catheters against paravertebral and epidural analgesia in patients with multiple RIB fractures. (30th August 2019) - Beard, L; Hillermann, C; Beard, E; Millerchip, S; Gao Smith, F; Veenith, T
Abstract : Background and aims: The analgesic efficacy of serratus anterior plane (SAP) block with catheter insertion was compared against thoracic epidural analgesia (TEA) and paravertebral analgesia (PA) in patients with multiple rib fractures (MRFs). Methods: Data were collected from patient notes on 203 participants who received either SAP, TEA or PA between 2016 and 2018 at two major trauma centres in the UK. Primary outcomes were change in inspiratory volumes (mls) and pain scores, which were measured on a numerical rating scale of 0–3 (0=no pain, 1=mild, 2=moderate, 3=severe). Paired t-test or ANOVA were conducted to compare pre/post block parameters and difference between groups. Institutional approval was obtained from both sites (GF0223/CARMS14833). Results: There was a significant increase in inspiratory volumes and reduction in pain scores in all three groups (inspiratory volumes: increase of 789 mls, P<0.001, pain: reduction of -1.40, P<0.001). the magnitude of this change was the same for SAP, TEA and PA. table 1 and figures 1 and 2 show the breakdown of results overall and for each group. Conclusions: Our research represents the first study to date that compares the analgesic effectiveness of SAP block to traditional methods of PA and TEA in patients with MRFs. the results reveal that the SAP block is comparable to TEA and PA analgesia in terms of reduction in pain scores and improvement in inspiratory volume post insertion. This study gives additional support to the promising new role of SAP blocks in this cohort especially when PA or TEA may be contraindicated.